[μ2-trans-1,2-Bis(pyridin-4-yl)ethene-κ2N:N′]bis{[1,2-bis(pyridin-4-yl)ethene-κN]bis[N-(2-hydroxyethyl)-N-isopropyldithiocarbamato-κ2S,S′]cadmium} acetonitrile tetrasolvate: crystal structure and Hirshfeld surface analysis - Jotani, Mukesh M.; Poplaukhin, Pavel; Arman, Hadi D.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The asymmetric unit of the title compound, [Cd2(C12H10N2)3(C6H12NOS2)4]·4C2H3N, comprises a CdII atom, two dithiocarbamate (dtc) anions, one and a half trans-1,2-dipyridin-4-ylethylene (bpe) molecules and two acetonitrile solvent molecules. The full binuclear complex is generated by the application of a centre of inversion. The dtc ligands are chelating, one bpe molecule coordinates in a monodentate mode while the other is bidentate bridging. The resulting cis-N2S4 coordination geometry is based on an octahedron. Supramolecular layers, sustained by hydroxy-O—H⋯O(hydroxy) and hydroxy-O—H⋯N(bpe) hydrogen bonding, interpenetrate to form a three-dimensional architecture; voids in this arrangement are occupied by the acetonitrile solvent molecules. Additional intermolecular interactions falling within the specified framework have been analysed by Hirshfeld surface analysis, including π–π interactions.